Rapid on‐site evaluation by endosonographer during endoscopic ultrasound‐guided fine needle aspiration for pancreatic solid masses. Issue 4 (25th March 2013) - Hayashi, Tsuyoshi; Ishiwatari, Hirotoshi; Yoshida, Makoto; Ono, Michihiro; Sato, Tsutomu; Miyanishi, Koji; Sato, Yasushi; Kobune, Masayoshi; Takimoto, Rishu; Mitsuhashi, Tomoko; Asanuma, Hiroko; Ogino, Jiro; et al.
Abstract Background and Aim Endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) is an established diagnostic method for patients with suspected pancreatic ductal carcinoma. Rapid on‐site evaluation (ROSE) has been reported to improve the accuracy. However, an on‐site cytopathologist is not routinely available in many institutions. One of the solutions may be ROSE by endosonographer. The aim was to examine whether diagnostic accuracy increases through ROSE by endosonographer using our cytological criteria. Methods Patients who underwent EUS‐FNA of solid pancreatic masses from January 2006 to August 2009 (n = 53, period 1) and September 2009 to April 2011 (n = 85, period 2) were retrospectively identified. Before initiating ROSE at the start of period 2, two endosonographers underwent training for cytological interpretation, which was focused on four cytological features of pancreatic ductal carcinoma: anisonucleosis, nuclear membrane irregularity, overlapping, and enlargement. During EUS‐FNA in period 2, endosonographers classified the Diff‐Quik smears under three atypical grades and evaluated the adequacy. All diagnoses were made by one pathologist without knowledge of clinical information. Results The rate of "inconclusive" diagnoses, interpreted as "suspicious, " "atypical, " and "inadequate for diagnosis" was reduced from 26.4% in period 1 to 8.2% in period 2 (P = 0.004). Moreover, diagnostic accuracy was increased from 69.2% in period 1 to 91.8% in period 2 (P < 0.001). Conclusions This cytological grading system used in ROSE by endosonographers is invaluable for the diagnosis of pancreatic solid masses.